RESISTANCE OF MORTAR WITH PPC CEMENT AND GEOPOLYMER MORTAR WITH WHITE SOIL SUBSTITUTION IN H2SO4 IMMERSION - Priastiwi, Yulita Arni; Hidayat, Arif; Tamrin, Rinaldo; Sendrika, Difa Bagus (Universitas Ibn Khaldun Bogor, 2021)
This study analyzes the effect of immersion of H2SO4 (sulfuric acid) solution with a concentration of 10% on porosity, density and compressive strength of mortar with PPC cement and geopolymer with white soil substitution mortar. The purpose of this study was to determine the resistance of mortar with PPC cement and geopolymer with white soil substitution mortar when immersed in 10% H2SO4 solution. The test object was 5x5x5 cm mortar with materials used including fly ash from PLTU Tanjung Jati B Jepara, white soil from Kupang, fine aggregate, water and alkaline activator in the form of a mixture of 8M NaOH and Na2SiO3 and also PPC cement. The composition of the geopolymer mortar mixture is 1binder: 3Fine Aggregate: 0,5Water-Binder Ratio, while the mortar with PPC cement is made with a composition of 1PPC: 3Fine Aggregate: 0,5Water-Cement Ratio. The geopolymer mortar was made in 6 variations with a white soil substitution percentage of 0-25% with an increase of 5% for each variation. Compressive strength testing using a compression test apparatus. The test results show that the variation in the percentage of white soil substitution has less effect on the size of the porosity value. As for the value of compressive strength and density, white soil substitution has an effect, the higher the white soil substitution, the higher the compressive strength and mortar density values. Geopolymer mortar was better to withstand 10% sulfuric acid solution, while mortar with PPC cement had no resistance to 10% sulfuric acid solution because it continued to deteriorate over the course of the day. The greatest compressive strength is in variation IV (15% white soil substitution) of 15,31 MPa at 28 days of age, while the smallest porosity and greatest density are in variation VI (25% white soil substitution) of 0,17% and 2,205 grams/cm3.